Preparation method and application of flexible nanoparticle smart hydrogel loaded with nicotinic acid
Patent Information
- Application Number
- CN202311558840.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-21
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-11-21
AI Technical Summary
然而手术内增压技术需要在术区解剖出可吻合的血管,临床中此处的血管往往是缺如的
[0025] This invention provides a method for preparing and applying a nicotinic acid-loaded flexible nanoparticle smart hydrogel. On one hand, this invention is the first to synthesize polymethyl methacrylate-butyl acrylate nanoparticles (P(MMA-BA)), giving the hydrogel a photonic bandgap effect. This means the hydrogel changes color with tension, allowing it to sense changes in skin flap tension. Alternatively, this photonic crystal hydrogel's response to changes in the photonic bandgap position in response to external stimuli can be converted into visible color changes, thus achieving semi-quantitative colorimetric detection of external stimuli. On the other hand, the introduction of boric acid bonds gives the hydrogel a pH response, resulting in better drug release in low-pH wound environments. Simultaneously, the nicotinic acid-loaded flexible nanoparticle smart hydrogel can locally deliver and release nicotinic acid. Conventional drug administration involves systemic administration, but insufficient angiogenesis in the Choke II region makes it difficult for systemic drugs to reach the Choke II region. Therefore, loading nicotinic acid onto the hydrogel allows for local application and release of nicotinic acid, avoiding the drawback of systemic drug administration's inability to reach the lesion.
Smart Images

Figure CN120420261B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomaterials technology, and in particular to a method for preparing and applying a flexible nanoparticle smart hydrogel loaded with nicotinic acid. Background Technology
[0002] Transregional perforator flaps are commonly used for repairing soft tissue defects of the limbs; however, distal necrosis of the flap remains a challenging problem. The perforator body is the basic anatomical unit of the perforator flap, which can be divided into three regions: the anatomical region originating from the source artery, the dynamic region adjacent to the anatomical region, and the potential region adjacent to the dynamic region. The flap survives relatively stably in the anatomical and dynamic regions, while necrosis often occurs in the potential region. The vessels that anastomose between adjacent vascular regions, with gradually decreasing diameters, are called choke vessels, and are extremely important for the survival of transregional perforator flaps. The anastomosis area of choke vessels between the anatomical and dynamic regions is called Choke I, and the anastomosis area between the dynamic and potential regions is called Choke II. Insufficient dilation and neovascularization in Choke II regions is one of the important causes of necrosis in the potential region of the flap; improving blood supply to Choke II is crucial for flap survival.
[0003] In recent years, to improve the survival rate of transregional perforator flaps, researchers have used techniques such as surgical flap inflation and drug intervention to dilate and / or promote angiogenesis in the Choke II region, thereby improving blood supply to the Choke II region and increasing the viable flap area. However, surgical inflation requires the dissection of anastomosable vessels in the surgical area, which is often absent in clinical practice. Drug intervention, with its advantages of high safety, minimal trauma, and less pain, has gradually become a research hotspot for flap enlargement and harvesting.
[0004] Many scholars both domestically and internationally have attempted to pretreat transregional perforator flaps with various vasoactive drugs, but all these studies have focused on systemic administration. Systemic administration often requires higher drug concentrations compared to local administration, while local administration can reduce side effects and is more targeted. Furthermore, local administration avoids drug interactions. Local drug delivery using hydrogel materials is one method to promote repair; therefore, developing efficient drug hydrogel delivery carriers that maintain drug activity during transport and controlled release to demonstrate excellent tissue repair capabilities is a key research focus in this field. Summary of the Invention
[0005] To address the aforementioned issues, this invention provides a method for preparing and applying a flexible nanoparticle smart hydrogel loaded with nicotinic acid.
[0006] In a first aspect, the present invention provides a method for preparing a flexible nanoparticle smart hydrogel loaded with nicotinic acid, the method comprising the following steps:
[0007] Polymethyl methacrylate-butyl acrylate nanoparticles were obtained;
[0008] The silk fibroin, N-hydroxysuccinimide, carbodiimide and 3-aminophenylboronic acid were subjected to an amidation reaction to obtain the silk fibroin-3-aminophenylboronic acid compound.
[0009] The polymethyl methacrylate-butyl acrylate nanoparticles, acrylamide, the silk fibroin-3-aminophenylboronic acid compound, and nicotinic acid were subjected to a photo-crosslinking and curing reaction to obtain a nicotinic acid-loaded flexible nanoparticle smart hydrogel.
[0010] Furthermore, the weight ratio of the polymethyl methacrylate-butyl acrylate nanoparticles, the acrylamide, the silk fibroin-3-aminophenylboronic acid compound, and the nicotinic acid is (2-8):(15-25):(15-20):(2-8).
[0011] Furthermore, the operating parameters of the photo-crosslinking curing reaction include: the weight of the photoinitiator added is 0.1 to 0.3 times the weight of the polymethyl methacrylate-butyl acrylate nanoparticles added, the light source is ultraviolet light, the irradiation time is 20s to 45s, and the irradiation dose is 70 to 90 UV.
[0012] Furthermore, the step of obtaining polymethyl methacrylate-butyl acrylate nanoparticles includes the following process:
[0013] Methyl methacrylate, butyl acrylate, ethylene glycol dimethacrylate, acrylic acid, and acrylamide are added to water and mixed to obtain the first mixture;
[0014] Under an inert gas atmosphere, the first mixture is heated and stirred for the first time, and then an aqueous solution containing ammonium persulfate and sodium polystyrene sulfonate is added for the second heating and stirring to obtain the second mixture;
[0015] The second mixture was centrifuged and filtered, the solid product was collected and washed to obtain the polymethyl methacrylate-butyl acrylate nanoparticles.
[0016] Further, the weight ratio of methyl methacrylate, butyl acrylate, ethylene glycol dimethacrylate, acrylic acid, acrylamide, ammonium persulfate, and sodium polystyrene sulfonate is (1.5–3.5):(2–3):(0.04–0.07):(0.1–0.3):(0.1–0.35):(0.1–0.3):(0.02–0.08); the operating parameters of the first heating and stirring include: a first heating and stirring temperature of 80–100°C and a first heating and stirring time of 0.3–0.7 hours; the operating parameters of the second heating and stirring include: a second heating and stirring temperature of 80–100°C and a second heating and stirring time of 7–10 hours.
[0017] Further, the step of amidating silk fibroin, N-hydroxysuccinimide, carbodiimide, and 3-aminophenylboronic acid to obtain the silk fibroin-3-aminophenylboronic acid compound includes the following processes:
[0018] Silk fibroin was dissolved in fatty acid methyl ester sulfonate buffer, and then N-hydroxysuccinimide and carbodiimide were added and stirred at room temperature to obtain the third mixture.
[0019] Under an inert gas atmosphere, 3-aminophenylboronic acid was added to the third mixture for amidation reaction. The product was collected and dialyzed in distilled water to obtain the silk fibroin-3-aminophenylboronic acid compound.
[0020] Further, the weight ratio of the silk fibroin, the N-hydroxysuccinimide, the carbodiimide and the 3-aminophenylboronic acid is (0.8-1.2):(0.8-1.2):(0.4-0.7):(1.0-1.5); the operating parameters of the amidation reaction include: the amidation reaction temperature is room temperature and the amidation reaction time is 10-14 hours.
[0021] In a second aspect, the present invention provides a flexible nanoparticle smart hydrogel loaded with nicotinic acid, wherein the flexible nanoparticle smart hydrogel loaded with nicotinic acid is prepared by the preparation method described in any one of the first aspects.
[0022] Thirdly, embodiments of this application provide the application of the nicotinic acid-loaded flexible nanoparticle smart hydrogel as described in any of the second aspects in the preparation of a drug, wherein the nicotinic acid-loaded flexible nanoparticle smart hydrogel serves as a drug carrier, and / or, nicotinic acid in the nicotinic acid-loaded flexible nanoparticle smart hydrogel serves as a drug efficacy component.
[0023] Fourthly, embodiments of this application provide a drug that promotes angiogenesis, the drug comprising the nicotinic acid-loaded flexible nanoparticle smart hydrogel as described in any of the second aspects.
[0024] The technical solutions provided in the embodiments of the present invention have at least the following advantages compared with the prior art:
[0025] This invention provides a method for preparing and applying a nicotinic acid-loaded flexible nanoparticle smart hydrogel. On one hand, this invention is the first to synthesize polymethyl methacrylate-butyl acrylate nanoparticles (P(MMA-BA)), giving the hydrogel a photonic bandgap effect. This means the hydrogel changes color with tension, allowing it to sense changes in skin flap tension. Alternatively, this photonic crystal hydrogel's response to changes in the photonic bandgap position in response to external stimuli can be converted into visible color changes, thus achieving semi-quantitative colorimetric detection of external stimuli. On the other hand, the introduction of boric acid bonds gives the hydrogel a pH response, resulting in better drug release in low-pH wound environments. Simultaneously, the nicotinic acid-loaded flexible nanoparticle smart hydrogel can locally deliver and release nicotinic acid. Conventional drug administration involves systemic administration, but insufficient angiogenesis in the Choke II region makes it difficult for systemic drugs to reach the Choke II region. Therefore, loading nicotinic acid onto the hydrogel allows for local application and release of nicotinic acid, avoiding the drawback of systemic drug administration's inability to reach the lesion.
[0026] In summary, the nicotinic acid-loaded flexible nanoparticle smart hydrogel provided by this invention has the functions of wet tissue adhesion, stretchability, sustained release of nicotinic acid, pH response, photonic bandgap effect, and angiogenesis promotion. It can be used as a drug carrier in the fields of drugs that promote angiogenesis and has broad practical application value. Attached Figure Description
[0027] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0028] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0029] Figure 1 This is a schematic flowchart illustrating a method for preparing a flexible nanoparticle smart hydrogel loaded with nicotinic acid, as provided in an embodiment of the present invention.
[0030] Figure 2 This is a schematic diagram of the preparation method of the flexible nanoparticle smart hydrogel loaded with nicotinic acid provided in Example 1 of the present invention.
[0031] Figure 3This is a physical photograph of the flexible nanoparticle smart hydrogel loaded with nicotinic acid provided in Embodiment 1 of the present invention.
[0032] Figure 4 Infrared spectrum of the flexible nanoparticle smart hydrogel loaded with nicotinic acid provided in Example 1 of the present invention.
[0033] Figure 5 XPS pattern of the flexible nanoparticle smart hydrogel loaded with nicotinic acid provided in Example 1 of the present invention.
[0034] Figure 6 The image shows the SEM pattern of the flexible nanoparticle smart hydrogel loaded with nicotinic acid provided in Example 1 of this invention.
[0035] Figure 7 The image shows the SEM pattern of P(MMA-BA) in the flexible nanoparticle smart hydrogel loaded with nicotinic acid provided in Example 1 of this invention.
[0036] Figure 8 The stress-strain test and rheological test results of the flexible nanoparticle smart hydrogel loaded with nicotinic acid provided in Example 1 of the present invention.
[0037] Figure 9 The test results are from Test Example 2 of this invention. Figure 1 .
[0038] Figure 10 The test results are from Test Example 2 of this invention. Figure 2 .
[0039] Figure 11 The test results are from Test Example 2 of this invention. Figure 3 .
[0040] Figure 12 The test results are from Test Example 2 of this invention. Figure 4 .
[0041] Figure 13 The test results are from Test Example 2 of this invention. Figure 5 . Detailed Implementation
[0042] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0043] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0044] In a first aspect, the present invention provides a flexible nanoparticle smart hydrogel loaded with nicotinic acid, such as... Figure 1 As shown, the preparation method includes the following steps:
[0045] Polymethyl methacrylate-butyl acrylate nanoparticles were obtained;
[0046] The silk fibroin, N-hydroxysuccinimide, carbodiimide and 3-aminophenylboronic acid were subjected to an amidation reaction to obtain the silk fibroin-3-aminophenylboronic acid compound.
[0047] The polymethyl methacrylate-butyl acrylate nanoparticles, acrylamide, the silk fibroin-3-aminophenylboronic acid compound, and nicotinic acid were subjected to a photo-crosslinking and curing reaction to obtain a nicotinic acid-loaded flexible nanoparticle smart hydrogel.
[0048] This invention provides a flexible nanoparticle smart hydrogel loaded with nicotinic acid. This flexible nanoparticle smart hydrogel loaded with nicotinic acid has the functions of wet tissue adhesion, stretchability, sustained release of nicotinic acid, pH response, photonic bandgap effect, and angiogenesis promotion. It can be used as a drug carrier in the fields of drugs that promote angiogenesis and has broad practical application value.
[0049] In this invention, a flexible nanoparticle-based smart hydrogel loaded with nicotinic acid can locally deliver and release nicotinic acid. Conventional drug administration involves systemic delivery, but insufficient angiogenesis in the Choke II region makes it difficult for systemically administered drugs to reach the Choke II region. Therefore, loading nicotinic acid onto the hydrogel allows for local application and release of nicotinic acid, avoiding the drawback of systemically administered drugs failing to reach the lesion. Furthermore, the term "smart" in this application refers to two aspects: firstly, the polymethyl methacrylate-butyl acrylate nanoparticles (P(MMA-BA)) give the hydrogel a photonic bandgap effect, meaning the hydrogel changes color with tension, allowing it to sense changes in flap tension. Alternatively, this photonic crystal hydrogel's response to changes in the photonic bandgap position in response to external stimuli can be translated into visible color changes, thus achieving semi-quantitative colorimetric detection of external stimuli; secondly, the introduction of boric acid bonds gives the hydrogel a pH response, resulting in better drug release rates in low-pH wound environments.
[0050] In this invention, polymethyl methacrylate-butyl acrylate nanoparticles (abbreviated as P(MMA-BA)) are used.
[0051] In some specific embodiments, the weight ratio of the polymethyl methacrylate-butyl acrylate nanoparticles, the acrylamide, the silk fibroin-3-aminophenylboronic acid compound, and the nicotinic acid is (2-8):(15-25):(15-20):(2-8).
[0052] In some specific embodiments, the operating parameters of the photo-crosslinking curing reaction include: the weight of the photoinitiator added is 0.1 to 0.3 times the weight of the polymethyl methacrylate-butyl acrylate nanoparticles added, the light source is ultraviolet light, the irradiation time is 20s to 45s, and the irradiation dose is 70 to 90 UV.
[0053] In some specific embodiments, the step of obtaining polymethyl methacrylate-butyl acrylate nanoparticles includes the following processes:
[0054] Methyl methacrylate (MMA), butyl acrylate (BA), ethylene glycol dimethacrylate (EGDMA), acrylic acid (AA), and acrylamide (AAM) were added to water and mixed to obtain the first mixture.
[0055] Under an inert gas atmosphere, the first mixture is heated and stirred for the first time, and then an aqueous solution containing ammonium persulfate (APS) and sodium polystyrene sulfonate (NaPSS) is added for the second heating and stirring to obtain the second mixture;
[0056] The second mixture was centrifuged and filtered, the solid product was collected and washed to obtain the polymethyl methacrylate-butyl acrylate nanoparticles.
[0057] In some specific embodiments, the weight ratio of methyl methacrylate, butyl acrylate, ethylene glycol dimethacrylate, acrylic acid, acrylamide, ammonium persulfate, and sodium polystyrene sulfonate is (1.5–3.5):(2–3):(0.04–0.07):(0.1–0.3):(0.1–0.35):(0.1–0.3):(0.02–0.08); the operating parameters of the first heating and stirring include: a first heating and stirring temperature of 80–100°C and a first heating and stirring time of 0.3–0.7 hours; the operating parameters of the second heating and stirring include: a second heating and stirring temperature of 80–100°C and a second heating and stirring time of 7–10 hours.
[0058] In some specific embodiments, the steps of amidation of silk fibroin (SF), N-hydroxysuccinimide (NHS), carbodiimide (EDC), and 3-aminophenylboronic acid (PBA) to obtain the silk fibroin-3-aminophenylboronic acid compound include the following processes:
[0059] Silk fibroin was dissolved in fatty acid methyl ester sulfonate buffer, and then N-hydroxysuccinimide and carbodiimide were added and stirred at room temperature to obtain the third mixture.
[0060] Under an inert gas atmosphere, 3-aminophenylboronic acid was added to the third mixture for amidation reaction. The product was collected and dialyzed in distilled water to obtain the silk fibroin-3-aminophenylboronic acid compound.
[0061] In some specific embodiments, the weight ratio of the silk fibroin, the N-hydroxysuccinimide, the carbodiimide, and the 3-aminophenylboronic acid is (0.8-1.2):(0.8-1.2):(0.4-0.7):(1.0-1.5); the operating parameters of the amidation reaction include: the amidation reaction temperature is room temperature, and the amidation reaction time is 10-14 hours.
[0062] It should be noted that, unless otherwise specified, the operation steps involved in the preparation method of the nicotinic acid-loaded flexible nanoparticle smart hydrogel provided in the embodiments of the present invention can be carried out in accordance with conventional operation in the field or with existing equipment according to the operation manual; at the same time, unless otherwise specified, the raw materials used in the preparation method can be commercially available products or self-made according to existing preparation processes.
[0063] Secondly, based on the same inventive concept, the present invention provides a flexible nanoparticle smart hydrogel loaded with nicotinic acid, wherein the flexible nanoparticle smart hydrogel loaded with nicotinic acid is prepared by the preparation method described in any one of the first aspects.
[0064] The nicotinic acid-loaded flexible nanoparticle smart hydrogel provided by this invention has the functions of wet tissue adhesion, stretchability, sustained release of nicotinic acid, pH response, photon band effect, and angiogenesis promotion. It can be used as a drug carrier in the fields of drugs that promote angiogenesis and has broad practical application value.
[0065] Thirdly, based on the same inventive concept, embodiments of this application provide the application of the nicotinic acid-loaded flexible nanoparticle smart hydrogel described in any of the second aspects in the preparation of drugs, wherein the nicotinic acid-loaded flexible nanoparticle smart hydrogel serves as a drug carrier, and / or, nicotinic acid in the nicotinic acid-loaded flexible nanoparticle smart hydrogel serves as a drug efficacy component.
[0066] Fourthly, based on the same inventive concept, embodiments of this application provide a drug that promotes angiogenesis, the drug comprising the nicotinic acid-loaded flexible nanoparticle smart hydrogel as described in any of the second aspects.
[0067] In some specific embodiments, the pharmaceutical active ingredient loaded on the drug carrier may also be an existing drug such as Danshen Hong or Tanshinone IIA.
[0068] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed according to national standards. If no corresponding national standard exists, then generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer are followed.
[0069] Example 1
[0070] This example provides a flexible nanoparticle smart hydrogel loaded with nicotinic acid, and its preparation schematic diagram is shown below. Figure 2 As shown, the specific steps include:
[0071] Step (1) Preparation of P(MMA-BA) particles: Mix 3 mL MMA, 3 mL BA, 50 μL EGDMA, 0.2 mL AA and 0.2 g AAM monomer with 60 mL deionized water; heat the mixture to 90 °C and stir for 0.5 hours under a nitrogen atmosphere; then add 4 mL of an aqueous solution containing 180 mg APS and 50 mg NaPSS to the mixture and continue the reaction for 8 hours; collect the product by centrifugation, wash it 3 times with deionized water to obtain P(MMA-BA) particles, and then disperse them in 20 mL of deionized water for later use;
[0072] Step (2) Preparation of SF-PBA (i.e., silk fibroin-3-aminophenylboronic acid compound): Dissolve 1.00 g SF in a solution of MES buffer at pH 5.5; then, add 0.95 g NHS and 0.58 g EDC at room temperature and stir for 30 minutes; subsequently, add 1.20 g PBA under N2 atmosphere and stir at constant temperature for 12 hours; dialyze the obtained product in distilled water (MWCO, molecular weight cutoff of 3500) for 3 days and freeze dry to obtain SF-PBA;
[0073] Step (3) Preparation of flexible nanoparticle smart hydrogel loaded with nicotinic acid: SF-PBA, AM, P(MMA-BA) particles obtained in step (2), nicotinic acid and photoinitiator 2959 are mixed and subjected to photo-crosslinking and curing reaction under ultraviolet light to form a hydrogel, denoted as PPSB-1; wherein, by weight percentage, the amount of each raw material added is: 20% SF-PBA, 5% P(MMA-BA) colloidal nanoparticles, 20% PAM, 1% 2959, 5% nicotinic acid; the photo-crosslinking and curing reaction is carried out for 30s and the light dose is 80UV.
[0074] Test Example 1
[0075] This example characterizes the nicotinic acid-loaded flexible nanoparticle smart hydrogel obtained in Example 1. The physical images, infrared spectra, and XPS spectra of the obtained nicotinic acid-loaded flexible nanoparticle smart hydrogel are shown below. Figure 3 , Figure 4 and Figure 5 As shown.
[0076] This example also includes surface morphology analysis of the obtained nicotinic acid-loaded flexible nanoparticle smart hydrogel. The hydrogel was frozen at -20°C for 12 hours, and then the water in the gel was removed using a freeze dryer. Scanning electron microscopy (SEM) was used to observe the cross-sectional morphology of the hydrogel and to study the internal cross-linked network structure. The SEM images of the nicotinic acid-loaded flexible nanoparticle smart hydrogel are shown below. Figure 6 As shown, the SEM image of P(MMA-BA) is as follows: Figure 7 As shown. By Figure 6 and Figure 7 It can be seen that the particle size of P(MMA-BA) is approximately 150 nm. Figure 7 The PPSB hydrogel exhibits a porous 3D structure.
[0077] This example also includes stress-strain and rheological tests on the obtained nicotinic acid-loaded flexible nanoparticle smart hydrogel, with results as follows: Figure 8 ( Figure 8 In the figure, 'e' represents the stress-strain test result. Figure 8 (H represents the rheological test results). Figure 8 It can be seen that: (1) PPSB hydrogel has better mechanical properties than PAM and PAM / SF-PBA; (2) the storage modulus G' of the hydrogel is greater than the loss modulus G”, indicating that the hydrogel is in a liquid state.
[0078] Test Example 2: Detection of swelling rate, degradation rate, and drug release of PPSB hydrogel
[0079] 2.1 Swelling rate test
[0080] The freeze-dried coating was weighed and labeled as WI. The sample was then placed in PBS buffer. Every hour, water was removed from the hydrogel surface using filter paper, and the weight was weighed and labeled WS. The swelling ratio (SR) was calculated using the following formula:
[0081] Expansion rate = (WS-WI) / WI × 100%.
[0082] 2.2 Degradation rate detection
[0083] The drug release effect was measured by ultraviolet absorbance. 0.1 g of hydrogel was dissolved in 10 mL of PBS at 37 °C and 100 rpm / min. 1 mL of supernatant was collected every hour and replaced with 1 mL of PBS. The absorbance was measured at λ = 280 nm using a UV spectrophotometer and calculated using a standard curve. To characterize the pH-controlled release effect of the coating, the hydrogel was placed in buffer solutions at pH 4.5 and 7.2 for 30 minutes, respectively. Subsequently, the pH response of the coating was measured using the method described above.
[0084] Adhesion test of PPSB hydrogel
[0085] Tensile shear tests were conducted on a tensile testing machine (FLR-303, Flora Automatic Technology, China) at a test speed of 10 mm / min according to ASTM F2255-05 (2015) to study the adhesion properties of the hydrogel. Tensile shear joints [length (L) × width (W) = 25 × 20 mm] were completely prepared by adding 500 mL of pre-adhesive solution between two glass plates. All samples were then pressed together with a 100 g weight and left to stand for 30 minutes.
[0086] PPSB hydrogel stretch response
[0087] Clamp both ends of the sheet-like gel and place a graduated steel ruler underneath. Then, begin stretching. After stretching, gradually release the grips to relieve stress. Record the entire process on video. Calculate the tensile strain at a specific moment based on the video footage, and record the structural color change at that moment using a fiber optic spectrometer.
[0088] PPSB hydrogel cytotoxicity assay
[0089] The cytotoxicity of the hydrogel was assessed using a CCK-8 assay kit. BMSC cells were resuscitated and passaged three times. The culture medium was discarded, and the cells were washed several times with PBS. 3 mL of trypsin was added, and the cells were incubated at 37°C for 3 minutes. Digestion was terminated with DMEM containing 10% FBS. After one wash, the cell suspension was seeded into 12-well plates and incubated at 37°C in a 5% CO2 incubator. Subsequently, 100 cell suspensions were transferred to new 96-well plates and incubated at 37°C for 24 and 48 hours. Then, 10 mL of CCK-8 was added to each well, and the cells were incubated for another 4 hours. The absorbance of the solution was measured at 450 nm using a Multiskan FC microplate reader (Thermo, US). Cell viability was calculated using the following formula:
[0090] Cell viability = (AT - A0) / (AC - A0) × 100% (2)
[0091] AT, A0, and AC represent the absorbance of the sample group, control group, and blank group, respectively.
[0092] Discard the culture medium from the 12-well plate, wash once with PBS, add the gel to the wells to form the membrane, and incubate at 37°C under 5% CO2. Remove the wells at predetermined time intervals (24, 48 hours) and collect the cell-conjugated gel in centrifuge tubes. Then, add 1 mL of PBS to each well, followed by 5 μL of fluorescein diacetate (FDA) and propidium iodide (PI) to each well to stain the cell membrane. After staining in the dark for 3 minutes, observe the stained cells under a fluorescence microscope.
[0093] Test results:
[0094] like Figure 9 As shown, Figure 9 In the figures: (a) swelling test results for each group of hydrogels; (b) degradation test results for each group of hydrogels; (c) pH response of PPSB hydrogels under different pH conditions due to different boric acid bond forms; (d) drug release results of the hydrogels obtained in Example 1 at different pH levels. Figure 9 It can be seen that PPSB hydrogel released 70% of the drug in pH 4.5 buffer solution after 32 hours, and released 20% of the drug in pH 7.2 buffer solution.
[0095] like Figure 10 As shown, Figure 10 In the image: (a) shows the adhesion test results of the hydrogel; (b) shows the adhesion strength test results of the hydrogel on different substrates; (c) shows the adhesion diagram of the hydrogel on different substrates. Figure 10It can be seen that PPSB hydrogel exhibits MPa-level adhesion strength on different substrates, ensuring that it does not fall off during the wound healing process.
[0096] like Figure 11 As shown, Figure 11 In the image: a) shows the test results of PPSB hydrogel for wound management; b) shows the spectral test results of the hydrogel; c) shows the continuous movement test results of the hydrogel. Figure 11 It is known that the hydrogel's color changes as the joint flexes, which can be used to indicate wound information. With continuous stretching of the hydrogel, the color change remains consistent even after several stretching cycles. The hydrogel exhibits a uniform structural color change during continuous stretching and maintains rapid color transition and recovery even after 20 cycles.
[0097] like Figure 12 As shown, Figure 12 In the image: a shows the cell viability assay results of the hydrogel; b shows the live / dead cell staining results of the hydrogel. Figure 12 It was found that none of the hydrogels showed any inhibitory effect on fibroblast growth after co-culturing for 1 day and 3 days. These results indicate that the hydrogels have good biocompatibility in biomedical applications.
[0098] like Figure 13 As shown, Figure 13 In the diagram: A shows the results of the hydrogel-induced survival test of rat skin flaps; B shows the results of increased blood flow to the skin flaps; C shows increased CD31 expression; D shows increased vascular density. Figure 13 It can be seen that PPSB promotes the survival of distal skin flaps in rats, which is related to the promotion of increased blood flow and angiogenesis in the Choke II area.
[0099] Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible subranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed subranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the range referred to.
[0100] In this invention, unless otherwise stated, directional terms such as "upper" and "lower" specifically refer to the drawing directions in the accompanying drawings. Furthermore, in the description of this invention, terms such as "comprising" and "including" mean "including but not limited to." In this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this document, "and / or" describes the relationship between related objects, indicating that three relationships may exist; for example, A and / or B can represent: A alone, A and B simultaneously, or B alone. A and B can be singular or plural. In this document, "at least one" means one or more, and "more than one" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c" or "at least one of a, b, and c" can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be a single or multiple.
[0101] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A method for preparing a flexible nanoparticle smart hydrogel loaded with nicotinic acid, characterized in that, The preparation method includes the following steps: Polymethyl methacrylate-butyl acrylate nanoparticles were obtained; The silk fibroin, N-hydroxysuccinimide, carbodiimide and 3-aminophenylboronic acid were subjected to an amidation reaction to obtain the silk fibroin-3-aminophenylboronic acid compound. The polymethyl methacrylate-butyl acrylate nanoparticles, acrylamide, the silk fibroin-3-aminophenylboronic acid compound, and nicotinic acid were subjected to a photo-crosslinking and curing reaction to obtain the nicotinic acid-loaded flexible nanoparticle smart hydrogel. The weight ratio of the polymethyl methacrylate-butyl acrylate nanoparticles, the acrylamide, the silk fibroin-3-aminophenylboronic acid compound and the nicotinic acid is (2~8):(15~25):(15~20):(2~8).
2. The method for preparing the nicotinic acid-loaded flexible nanoparticle smart hydrogel according to claim 1, characterized in that, The operating parameters of the photo-crosslinking curing reaction include: the weight of the photoinitiator added is 0.1 to 0.3 times the weight of the polymethyl methacrylate-butyl acrylate nanoparticles added; the light source is ultraviolet light; the irradiation time is 20s to 45s; and the irradiation dose is 70 to 90 UV.
3. The method for preparing the nicotinic acid-loaded flexible nanoparticle smart hydrogel according to claim 1, characterized in that, The steps for obtaining polymethyl methacrylate-butyl acrylate nanoparticles include the following processes: Methyl methacrylate, butyl acrylate, ethylene glycol dimethacrylate, acrylic acid, and acrylamide are added to water and mixed to obtain the first mixture; Under an inert gas atmosphere, the first mixture is heated and stirred for the first time, and then an aqueous solution containing ammonium persulfate and sodium polystyrene sulfonate is added for the second heating and stirring to obtain the second mixture; The second mixture was centrifuged and filtered, the solid product was collected and washed to obtain the polymethyl methacrylate-butyl acrylate nanoparticles.
4. The method for preparing the nicotinic acid-loaded flexible nanoparticle smart hydrogel according to claim 3, characterized in that, The weight ratio of the methyl methacrylate, butyl acrylate, ethylene glycol dimethacrylate, acrylic acid, acrylamide, ammonium persulfate, and sodium polystyrene sulfonate is (1.5~3.5):(2~3):(0.04~0.07):(0.1~0.3):(0.1~0.35):(0.1~0.3):(0.02~0.08); the operating parameters of the first heating and stirring include: a first heating and stirring temperature of 80~100℃ and a first heating and stirring time of 0.3~0.7 hours; the operating parameters of the second heating and stirring include: a second heating and stirring temperature of 80~100℃ and a second heating and stirring time of 7~10 hours.
5. The method for preparing the nicotinic acid-loaded flexible nanoparticle smart hydrogel according to claim 1, characterized in that, The steps for amidating silk fibroin, N-hydroxysuccinimide, carbodiimide, and 3-aminophenylboronic acid to obtain the silk fibroin-3-aminophenylboronic acid compound include the following processes: Silk fibroin was dissolved in fatty acid methyl ester sulfonate buffer, and then N-hydroxysuccinimide and carbodiimide were added and stirred at room temperature to obtain the third mixture. Under an inert gas atmosphere, 3-aminophenylboronic acid was added to the third mixture for amidation reaction. The product was collected and dialyzed in distilled water to obtain the silk fibroin-3-aminophenylboronic acid compound.
6. The method for preparing the nicotinic acid-loaded flexible nanoparticle smart hydrogel according to claim 5, characterized in that, The weight ratio of the silk fibroin, the N-hydroxysuccinimide, the carbodiimide, and the 3-aminophenylboronic acid is (0.8~1.2):(0.8~1.2):(0.4~0.7):(1.0~1.5); the operating parameters of the amidation reaction include: the amidation reaction temperature is room temperature, and the amidation reaction time is 10~14 hours.
7. A flexible nanoparticle smart hydrogel loaded with nicotinic acid, characterized in that, The nicotinic acid-loaded flexible nanoparticle smart hydrogel is prepared by the preparation method described in any one of claims 1 to 6.
8. The application of the nicotinic acid-loaded flexible nanoparticle smart hydrogel according to claim 7 in the preparation of pharmaceuticals, characterized in that, The nicotinic acid-loaded flexible nanoparticle smart hydrogel serves as a drug carrier, and / or, nicotinic acid in the nicotinic acid-loaded flexible nanoparticle smart hydrogel serves as a drug efficacy component.
9. A drug that promotes angiogenesis, characterized in that, The drug comprises the nicotinic acid-loaded flexible nanoparticle smart hydrogel of claim 7.
Citation Information
Patent Citations
Gelatin-silk fibroin hydrogel loaded with adipose-derived stem cells and plasma as well as preparation method and application of gelatin-silk fibroin hydrogel
CN113045717A
Silk fibroin / hyaluronic acid composite hydrogel as well as preparation method and application thereof
CN114524953A